2021
DOI: 10.3389/frobt.2020.586707
|View full text |Cite|
|
Sign up to set email alerts
|

Deep Learning-Based Haptic Guidance for Surgical Skills Transfer

Abstract: Having a trusted and useful system that helps to diminish the risk of medical errors and facilitate the improvement of quality in the medical education is indispensable. Thousands of surgical errors are occurred annually with high adverse event rate, despite inordinate number of devised patients safety initiatives. Inadvertently or otherwise, surgeons play a critical role in the aforementioned errors. Training surgeons is one of the most crucial and delicate parts of medical education and needs more attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Kaluschke et al [140] demonstrated a novel algorithm for material removal based on the god-object method and implemented their algorithm on a Kuka LBR robot for 6DOF high-force feedback (up to 200N). Fekri et al [141] used a recursive neural network with LSTM architecture to capture expert behavior during surgical drilling. This behavior was intended for the haptic guidance of novice surgeons during training.…”
Section: E Haptic Feedbackmentioning
confidence: 99%
“…Kaluschke et al [140] demonstrated a novel algorithm for material removal based on the god-object method and implemented their algorithm on a Kuka LBR robot for 6DOF high-force feedback (up to 200N). Fekri et al [141] used a recursive neural network with LSTM architecture to capture expert behavior during surgical drilling. This behavior was intended for the haptic guidance of novice surgeons during training.…”
Section: E Haptic Feedbackmentioning
confidence: 99%
“…Previously researchers have estimated surgical skills using i)kinematic data and convolutional neural network [ 9 ], ii) kinematic data as putative markers and deep neural networks [ 10 ], iii) virtual reality spinal task and machine learning algorithms (support vector machines, k-nearest neighbors, least discriminant analysis, naïve bayes and decision tree) [ 11 ], iv) image processing and deep neural network during robotic surgery [ 12 14 ], v) kinematic data from da Vinci robot and global rating score and machine learning (kNN, logistic regression, SVM) [ 15 ]. Recently deep learning-based haptic guidance systems have been used for surgical skill development [ 16 ]. Moreover, it is unknown which features from wearable sensors such as EMG and accelerometers could contribute more to skill identification.…”
Section: Introductionmentioning
confidence: 99%